Integrasi Sistem Hardware Pada Alat Real-Time Heart Rate Variability Monitor Menggunakan Pulse Sensor Max30102 - Pratama, Fredy; Rizal, Achmad; Barri, Muhammad Hablul (eProceedings of Engineering, 2024)
[1] D. A. Ryfai,